Pertanggungjawaban Bank Terhadap Nasabah Dalam Layanan Perbankan Digital - Imam Safi’i, Mohammad; Winiari Wahyuningtyas, yuli (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2022)
This study aims to analyze the legal rules related to the existence of digital banking as a form of service innovation carried out by banks and analyze the forms of legal protection and accountability provided to customers in the use of digital banking. This study uses a normative legal research type. Based on the research, the results show that there are no specific legal regulations in the implementation of digital banking. This is because the Banking Law does not discuss the provisions for digital banking activities. The responsibility of the bank if the customer is dissatisfied both verbally and in writing due to loss or potential material loss in the financial services sector, the customer can file a complaint. Customers who suffer losses due to cybercrimes are entitled to compensation as a form of responsibility from the bank as long as it is not the customer's negligence. If the negligence is caused by the bank concerned, the bank's negligence can be prosecuted as an unlawful act.